2014
DOI: 10.1016/j.ecoenv.2014.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Ethoprophos fate on soil–water interface and effects on non-target terrestrial and aquatic biota under Mediterranean crop-based scenarios

Abstract: The present study aimed to assess the environmental fate of the insecticide and nematicide ethoprophos in the soil-water interface following the pesticide application in simulated maize and potato crops under Mediterranean agricultural conditions, particularly of irrigation. Focus was given to the soil-water transfer pathways (leaching and runoff), to the pesticide transport in soil between pesticide application (crop row) and non-application areas (between crop rows), as well as to toxic effects of the variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Imidacloprid, dimethoate and pirimicarb are used to control wheat aphids (Neubauer et al, 1983;Niehoff and Poehling, 1995;Yuan et al, 2020); fosthiazate, chlorantraniliprole and ethoprophos are used to control soil nematodes (Huang et al, 2019;Leitão et al, 2014). HPLC grade acetonitrile (ACN) was obtained from Sigma Aldrich (Steinheim, Germany).…”
Section: Chemicalsmentioning
confidence: 99%
“…Imidacloprid, dimethoate and pirimicarb are used to control wheat aphids (Neubauer et al, 1983;Niehoff and Poehling, 1995;Yuan et al, 2020); fosthiazate, chlorantraniliprole and ethoprophos are used to control soil nematodes (Huang et al, 2019;Leitão et al, 2014). HPLC grade acetonitrile (ACN) was obtained from Sigma Aldrich (Steinheim, Germany).…”
Section: Chemicalsmentioning
confidence: 99%
“…Among these, fumigants and synthetic organic nematicides are the most generally applied and these are costly and may potentially pollute the environment (Aballay et al, 2001). In fact, excessive or deficient nematicide applications happen often, and show unpredictable results (Leitao et al, 2014). Thus, this research will be focused in nematicide detection and modeling.…”
Section: Introductionmentioning
confidence: 99%
“…kg À1 d.w., respectively). These authors reported negative effects of ethoprophos on F. candida and E. andrei reproduction upon exposure to soils collected from a greenhouse experiment [109]. F. candida reproduction was also affected by chlorantraniliprole, with lower toxicity in soils with higher organic matter content.…”
Section: Effects Of Insecticides At Individual and Population Levelsmentioning
confidence: 96%